2009
DOI: 10.1152/ajpgi.90428.2008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of curcumin on acidic pH-induced expression of IL-6 and IL-8 in human esophageal epithelial cells (HET-1A): role of PKC, MAPKs, and NF-κB

Abstract: Human esophageal epithelial cells play a key role in esophageal inflammation in response to acidic pH during gastroesophageal reflux disease (GERD), increasing secretion of IL-6 and IL-8. The mechanisms underlying IL-6 and IL-8 expression and secretion in esophageal epithelial cells after acid stimulation are not well characterized. We investigated the role of PKC, MAPK, and NF-kappaB signaling pathways and transcriptional regulation of IL-6 and IL-8 expression in HET-1A cells exposed to acid. Exposure of HET-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
53
3
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 29 publications
3
53
3
1
Order By: Relevance
“…Previous research using esophageal monolayer cells showed that weak acid could upregulate IL-8 gene expression (18,28). However, in our model, 24 h continuous weak acid (pH 4, 5, and 6) apical stimulation did not affect IL-8 production or TEER.…”
Section: Discussioncontrasting
confidence: 84%
“…Previous research using esophageal monolayer cells showed that weak acid could upregulate IL-8 gene expression (18,28). However, in our model, 24 h continuous weak acid (pH 4, 5, and 6) apical stimulation did not affect IL-8 production or TEER.…”
Section: Discussioncontrasting
confidence: 84%
“…COX-2 inhibitors such as celecoxib significantly reduced the severity of chronic esophagitis (Hayakawa et al, 2006). Nuclear factor-kappa B, mitogen-activated protein kinases and protein kinase C activation are known to be involved in the regulation of acid-induced upregulation of these inflammatory mediators in vitro (Rafiee et al, 2009). In the present study, serum levels of TNF-α and iNOS and COX-2 protein expressions in esophageal tissues were increased by RE, and CGA attenuated these increases.…”
Section: Discussionsupporting
confidence: 51%
“…Total cell extracts were prepared and subjected to Western blotting, as previously described (40). Cytoplasmic and nuclear fractions were prepared using the NE-PER kit according to the manufacturer's protocol (Pierce/Thermo Scientific, Rockford, IL).…”
Section: Methodsmentioning
confidence: 99%
“…Mucosal biopsies of equal size were cultured in 0.5 ml of RPMI medium for 24 h, as previously described (40). Dkk1 secretion was assessed in tissue and cell culture media by ELISA (R & D Systems) according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%